Editors' Choice—The Photoelectrochemical and Photocatalytic Properties of Tantalum Oxide and Tantalum Nitride. Issue 5 (1st January 2019) - Khanal, Vijay; Irani, Rowshanak; Fiechter, Sebastian; Abdi, Fatwa F.; Subramanian, Vaidyanathan (Ravi)
Abstract : The surfactant-assisted synthesis of tantalum oxide nanoparticles (Ta2 O5 ), its subsequent nitridation to form tantalum nitride (Ta3 N5 ), and the evaluation of the photoactivity of these nanoparticles, are presented. The surface, optical, and compositional characterization of the in-house synthesized photocatalysts indicate spherical nanoparticles with ϕ = 30 nm Ta2 O5 and ϕ = 30 nm Ta3 N5  with the latter photocatalysts showing absorbance onset at ∼ 630 nm. Photoelectrochemical analysis of the various photocatalyst films using chronoamperometry, linear sweep voltammetry, and impedance measurements attribute an improved photoactivity with the in-house catalysts to better charge generation, transport, and utilization. Initial results using Ta2 O5 and Ta3 N5 demonstrate photocatalytic activity toward conversion of colored pollutants.